Source apportionment of organic carbon and black carbon in the surface sediments of the Pearl River Estuary and its adjacent South China Sea: insight from stable carbon and nitrogen isotopes - Cao, Ruixue; Lao, Qibin; Huang, Chao; Han, Jiajun; Jin, Guangzhe; Lu, Xuan; Cai, Minggang; Chen, Chunqing; Chen, Fajin (Frontiers in Marine Science, 2024)
Coastal estuaries and adjacent continental shelf seas constitute vital global carbon reservoirs, and the sources and transformations of organic carbon in these regions are crucial to global biogeochemical cycles and climate change. This study investigated the total organic carbon (TOC), total nitrogen (TN), black carbon (BC), and their stable carbon and nitrogen isotopes (δ15NTN, δ13CTOC, δ13CBC) in the surface sediments of the Pearl River Estuary (PRE) and its adjacent northern South China Sea (NSCS) aiming to assess the impact of human activities on organic carbon dynamics in these areas. Results showed that the highest TOC concentrations occurred in the inner PRE due to intense human activities, and decreased seaward. The west side of the PRE exhibited higher TOC levels than the east side, which was attributed to differences in hydrodynamic processes and human activities. The westward flow of the Pearl River diluted water, which carried terrestrial organic matter inputs due to the influence of the Coriolis effect and intense local human activities, was a primary contributor to higher TOC levels on the west side (terrestrial source). In contrast, increased productivity and intensive mariculture activities on the east side predominated as sources of organic matter (marine source). Similar to the TOC, BC and TN sources were mainly influenced by human activities. δ15NTN distribution shows that TN in the east side of PRE mainly originated from industrial wastewater input from the Pearl River, while in the east side TN was mainly from domestic sewage discharge. Additionally, BC sources have shifted from primarily biomass combustion in the 1990s to fossil fuel emissions presently. Isotopic analysis revealed that over 70% of BC originated from fossil fuel inputs and C3 plant combustion, highlighting the significant influence of human activities in the PRE and adjacent NSCS, and underscoring the need for effective management and protection of the eco-environment in these regions.